2018
DOI: 10.1002/pssa.201700740
|View full text |Cite
|
Sign up to set email alerts
|

Impedimetric Sensing of DNA with Silicon Nanowire Transistors as Alternative Transducer Principle

Abstract: Silicon nanowires (SiNW) are highly sensitive to biomolecules. In some publications, changes of SiNW conductance in relation to their concentration levels are displayed. Upon binding, biomolecule charges change the surface potential and, thereby, the SiNW conductance. We discussed earlier that SiNWs can be regarded as long-channel, ion-sensitive field-effect transistors (ISFETs). The choice of a stable working point is important and defines the SiNW conductance. The common detection principle is based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 70 publications
(110 reference statements)
1
36
0
Order By: Relevance
“…In recent years, silicon nanowires (SiNWs) have aroused tremendous attention worldwide thanks to the following outstanding features: (1) Environment-friendly as second most earth-abundant materials; (2) unique dimensional structures (1 D); (3) interesting electrical and optical properties compared to bare silicon; (4) affordable fabrication; and (5) potential applications in several fields [1][2][3][4][5]. The various applications of these nanostructures may include lithium-ion batteries [6], biochemical sensors [7,8], electronics [9], catalysis [10], and solar cells [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, silicon nanowires (SiNWs) have aroused tremendous attention worldwide thanks to the following outstanding features: (1) Environment-friendly as second most earth-abundant materials; (2) unique dimensional structures (1 D); (3) interesting electrical and optical properties compared to bare silicon; (4) affordable fabrication; and (5) potential applications in several fields [1][2][3][4][5]. The various applications of these nanostructures may include lithium-ion batteries [6], biochemical sensors [7,8], electronics [9], catalysis [10], and solar cells [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nanowire (SiNW), which is a typical of one-dimensional semiconductor nanomaterial, can play important roles in nanoelectronic devices [1] , biochemical sensors [2,3] , and lithium-ion batteries (LIBs) [4,5] . In past decades, it has been reported that SiNWs can facilitate axial charge transfer and shorten radial Li + diffusion distance due to their one-dimensional characteristics, and are thus considered to be an interesting and promising new negative electrode material for LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[182] They suggested that at high frequencies the ions do not have enough time to form the EDL, and the fluctuating dipoles of the analyte modulate the surface potential of the nanotube. [41] The measurements were done at 100 kHz, where the frequency-dependent transconductance was at its maximum. Later, Laborde et al [183] proved it as a feasible technique with CMOS chips, imaging the attachment and movement of cells in real time in growth medium.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%
“…Finally, Si/ SiO x offers the chemistry possibilities for easy integration of biological receptors and more specific detection. [35][36][37] Many of them, including alternative fabrication [38][39][40] and measuring [37,41,42] methods, will be reviewed here. [31] In a classical metal-oxide-semiconductor field-effect transistor (MOSFET), the gate terminal is in direct contact with a thin dielectric layer that surrounds the semiconductor channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation